Assessment of adequacy and determinants of HIV related knowledge among senior school students in public schools in Abakaliki Southeast Nigeria - Maria-Lauretta Chito Orji; Ngozi Appolonia Ifebunandu; Chinwe Ifeoma Joe-Akunne; Mmeremikwu Appolus Chidiebere; Stella Echefu; Justus Ndulue Eze (Scientific Reports)
Abstract Misinformation, under-information, and disinformation regarding HIV among adolescents may be associated with a high prevalence of HIV among adolescents and young adults. The source of the HIV-related knowledge determines the accuracy and comprehensiveness of the information received. This study aimed to assess the adequacy (accuracy and comprehensive) of HIV-related knowledge and its determinants among senior school students in Abakaliki. A cross-sectional observational study that recruited 1,200 students from two public schools in Abakaliki, between December 2023 and May 2024. A pre-tested structured self-administered questionnaire comprising 10 questions was used to assess the adequacy of knowledge among students. These questions cut across the knowledge of the meaning of HIV/AIDS, its aetiology, risk factors, modes of transmission, prevention, the knowledge that an infected person may look healthy, testing, and treatment. Adequacy of HIV-related knowledge was denoted by a mean score of 6 and above. A multivariate analysis using a logistic regression model was used to determine the factors that predicted the adequacy of knowledge of HIV among students. The level of statistical significance was set at p < 0.05. A total of 687 (57.3%) and 442 (36.8%) of the students were within the 14-16- and 17-19-year age groups. More females (773/1,200, 64.4.0%) than males were recruited into the study. The adequacy of HIV knowledge was observed in 552 (46.0%) of the 1,200 students, with a mean knowledge score of 5.32 ± 2.3. Age groups, 14–16 years (95%CI = 1.27–3.54, AOR = 2.12, p = 0.004), and 17–19 years (95%CI = 1.09–3.12 AOR = 1.85, p = 0.015), students whose caregivers earned less than ₦30,000 (95%CI = 1.32–2.64, AOR = 1.87, p = < 0.001), school as source of knowledge (95%CI = 1.37–8.86, AOR = 3.48, p = 0.009), and the school attended (95%CI = 0.48–0.78, AOR = 0.61, p = < 0.001), were determinants of adequacy of HIV-related knowledge. In conclusion, HIV-related knowledge among senior secondary school students in public schools was observed to be inadequate.